Bacillus licheniformis SA03 Confers Increased Saline–Alkaline Tolerance in Chrysanthemum Plants by Induction of Abscisic Acid Accumulation - Zhou, Cheng; Zhu, Lin; Xie, Yue; Li, Feiyue; Xiao, Xin; Ma, Zhongyou; Wang, Jianfei (Frontiers in Plant Science, 2017)
Soil saline-alkalization is a major abiotic stress that leads to low iron (Fe) availability and high toxicity of sodium ions (Na+) for plants. It has recently been shown that plant growth promoting rhizobacteria (PGPR) can enhance the ability of plants to tolerate multiple abiotic stresses such as drought, salinity, and nutrient deficiency. However, the possible involvement of PGPR in improving saline-alkaline tolerance of plants and the underlying mechanisms remain largely unknown. In this study, we investigated the effects of Bacillus licheniformis (strain SA03) on the growth of Chrysanthemum plants under saline-alkaline conditions. Our results revealed that inoculation with SA03 alleviated saline-alkaline stress in plants with increased survival rates, photosynthesis and biomass. The inoculated plants accumulated more Fe and lower Na+ concentrations under saline-alkaline stress compared with the non-inoculated plants. RNA-Sequencing analyses further revealed that SA03 significantly activated abiotic stress- and Fe acquisition-related pathways in the stress-treated plants. However, SA03 failed to increase saline-alkaline tolerance in plants when cellular abscisic acid (ABA) and nitric oxide (NO) synthesis were inhibited by treatment with fluridone (FLU) and 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (c-PTIO), respectively. Importantly, we also found that NO acted downstream of SA03-induced ABA to activate a series of adaptive responses in plants under saline-alkaline stress. These findings demonstrated the potential roles of B. licheniformis SA03 in enhancing saline-alkaline tolerance of plants and highlighted the intricate integration of microbial signaling in regulating cellular Fe and Na+ accumulation.